A method for solidifying monazite waste residues

CN117964295BActive Publication Date: 2026-10-20THE FOURTH INST OF NUCLEAR ENG OF CNNC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311670893.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2026-10-20
Estimated Expiration
2043-12-07

AI Technical Summary

Technical Problem

但是含有大量钍和铀的独居石渣被存放起来未得到有效利用,成为对环境不利的放射性废渣

Benefits of technology

[0019]本发明提供了一种独居石废渣的固化方法,包括以下步骤:将水泥、独居石废渣、外加剂和水混合,得到砂浆;将所述砂浆进行固化,得到固化后的独居石废渣。本发明利用水泥对独居石废渣进行固化,能够有效的实现独居石废渣的固化处理;且得到的固化材料具有优异的力学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application belongs to the technical field of radioactive waste residue treatment, and particularly relates to a monazite waste residue solidification method. The application provides a monazite waste residue solidification method, which comprises the following steps: mixing cement, monazite waste residue, an additive and water to obtain mortar; and solidifying the mortar to obtain solidified monazite waste residue. The monazite waste residue is solidified by using cement, so that the solidification treatment of the monazite waste residue can be effectively realized; and the obtained solidified material has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of radioactive waste treatment technology, specifically relating to a method for solidifying monazite waste. Background Technology

[0002] Monazite is one of the most widely distributed and important rare earth minerals. Its composition is mainly light rare earth elements, typically containing 60%–65% REO, 21%–26% P2O5, 5%–10% ThO2, 0.2%–0.6% U3O8, and trace amounts of radium. Monazite has a wide range of sources, existing not only as a single mineral but also as a byproduct of the production of zircon sand, ilmenite, and rutile. China has abundant monazite reserves; in the largest rare earth mine—the Bayan Obo rare earth mine in Baotou—monazite accounts for 10%–50%, and this proportion is unrelated to the rare earth grade.

[0003] However, for a long time, monazite concentrate has only been used to extract rare earth elements and phosphorus. Current processes generate approximately 600 kg of monazite waste for every ton of rare earth element (REO) produced. This waste contains 7%–18% REO, while ThO2 and U3O8 are enriched to 16%–28% and 0.6%–1.2%, respectively. However, this monazite waste, containing large amounts of thorium and uranium, is stored without effective utilization, becoming radioactive waste detrimental to the environment.

[0004] The formation of monazite is inevitable, therefore, research on the solidification of monazite is of great significance. Summary of the Invention

[0005] The purpose of this invention is to provide a method for solidifying monazite waste residue. This invention can effectively solidify monazite waste residue, and the resulting solidified material has excellent mechanical properties.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] This invention provides a method for solidifying monazite waste, comprising the following steps:

[0008] Cement, monazite waste, additives and water are mixed to obtain mortar;

[0009] The mortar is solidified to obtain solidified monazite waste.

[0010] Preferably, the mass ratio of the cement, monazite waste, admixture and water is 1:5 to 8:0.015:0.45 to 2.0.

[0011] Preferably, the admixture includes a naphthalene-based water-reducing agent.

[0012] Preferably, the cement comprises ordinary Portland cement.

[0013] Preferably, the mixed raw materials also include a reinforcing agent, which includes fly ash and / or blast furnace slag.

[0014] Preferably, the mass ratio of the cement to the reinforcing agent is 1:1.

[0015] Preferably, the water-cement ratio of the mortar is 0.45 to 2.0.

[0016] Preferably, the mixing includes: first mixing the cement, monazite waste and admixture to obtain a first mixture; and second mixing the first mixture with water.

[0017] Preferably, both the first and second mixing are carried out under stirring conditions; the first mixing time is 5 minutes; and the second mixing time is 15 minutes.

[0018] Preferably, after curing, the solid material is further cured; the curing temperature is 18-22°C, the curing time is 14-56 days, and the relative humidity of the curing is ≥95%.

[0019] This invention provides a method for solidifying monazite waste residue, comprising the following steps: mixing cement, monazite waste residue, additives, and water to obtain mortar; and solidifying the mortar to obtain solidified monazite waste residue. This invention utilizes cement to solidify monazite waste residue, effectively achieving solidification treatment; and the resulting solidified material possesses excellent mechanical properties. Detailed Implementation

[0020] This invention provides a method for solidifying monazite waste, comprising the following steps:

[0021] Cement, monazite waste, additives and water are mixed to obtain mortar;

[0022] The mortar is solidified to obtain solidified monazite waste.

[0023] In this invention, unless otherwise specified, all raw materials are commercially available products well known to those skilled in the art.

[0024] This invention mixes cement, monazite waste, additives and water to obtain mortar.

[0025] In this invention, the mass ratio of cement, monazite waste, admixture and water is preferably 1:5 to 8:0.015:0.45 to 2.0, more preferably 1:5 to 8:0.015:1.06, and even more preferably 1:6 to 7:0.015:1.06.

[0026] In this invention, the cement preferably comprises ordinary Portland cement, and more preferably PO 42.5 Portland cement. In this invention, the ordinary Portland cement is a hydraulic cementitious material made by grinding Portland cement clinker, 5%–20% of admixtures, and an appropriate amount of gypsum. It possesses characteristics such as high strength, high heat of hydration, good frost resistance, low shrinkage, good wear resistance, good carbonation resistance, poor corrosion resistance, and poor high-temperature resistance.

[0027] In this invention, the particle size of the monazite waste is preferably 0.05 to 0.074 mm.

[0028] In this invention, the admixture preferably includes a naphthalene-based water-reducing agent.

[0029] In this invention, the mixed raw materials preferably also include a reinforcing agent, which preferably includes fly ash and / or blast furnace slag. In this invention, the mass ratio of cement to reinforcing agent is preferably 1:1. In this invention, the particle size of the reinforcing agent is preferably 0.005–0.3 mm. In this invention, the particle size of the fly ash is preferably 0.045–0.3 mm; the particle size of the blast furnace slag is preferably 0.005–0.05 mm.

[0030] In this invention, the water-cement ratio of the mortar is preferably 0.45 to 2.0, and more preferably 1.06.

[0031] In this invention, the mixing preferably includes: first mixing the cement, monazite waste and admixture to obtain a first mixture; and second mixing the first mixture with water.

[0032] In this invention, both the first mixing and the second mixing are preferably carried out under stirring conditions; the first mixing time is preferably 5 minutes; and the second mixing time is preferably 15 minutes.

[0033] In this invention, when the mixed raw materials also include a reinforcing agent, it is preferable to first mix the reinforcing agent with cement, monazite waste and admixtures.

[0034] After obtaining the mortar, the present invention solidifies the mortar to obtain solidified monazite waste residue.

[0035] The present invention does not impose any particular limitation on the curing process; any process well known to those skilled in the art can be used. In a specific embodiment of the present invention, the curing process preferably includes: placing the mortar in a molding mold, then placing the molding mold on a vibrating table for vibration until the air bubbles in the mortar disappear, and then placing the mold in a cool place to air dry. The present invention does not impose any particular limitation on the size of the molding mold; any size well known to those skilled in the art can be used. After curing, the present invention also preferably includes a demolding process.

[0036] After curing, the present invention preferably further includes curing the obtained solid material. In the present invention, the curing temperature is preferably 18-22°C, the curing time is preferably 14-56 days, and the relative humidity of the curing is preferably ≥95%.

[0037] To further illustrate the present invention, the following detailed description of a solidification method for monazite waste provided by the present invention is provided in conjunction with embodiments, but these should not be construed as limiting the scope of protection of the present invention.

[0038] Examples 1-9

[0039] Prepare materials according to the proportions in Table 1; the cement is PO 42.5 silicate cement, the particle size of monazite waste is 0.05-0.074mm, the particle size of fly ash is 0.045-0.3mm, and the particle size of blast furnace slag is 0.005-0.05mm.

[0040] Preparation method: Mix the raw materials except water, stir for 5 minutes, add water, and continue stirring for 15 minutes to obtain mortar;

[0041] Place the obtained mortar into a molding mold, then place the molding mold on a vibrating table and vibrate it until the air bubbles in the mortar disappear. After that, place the mold in a cool place to air dry.

[0042] The molded material is demolded and then placed in a curing box with a temperature of 20±2℃ and a relative humidity of ≥95% for 14 days to obtain solidified monazite waste.

[0043] Table 1. Ingredients for Examples 1-9 (Unit: parts by mass)

[0044] Example 1 1 8.0 0.015 -- -- 1.06 Example 2 1 6.5 0.015 -- -- 1.06 Example 3 1 5.0 0.015 -- -- 1.06 Example 4 1 8.0 0.015 -- 1 1.06 Example 5 1 6.5 0.015 -- 1 1.06 Example 6 1 5.0 0.015 -- 1 1.06 Example 7 1 8.0 0.015 1 -- 1.06 Example 8 1 6.5 0.015 1 -- 1.06 Example 9 1 5.0 0.015 1 -- 1.06

[0045] Performance testing

[0046] I. Compressive Strength Test

[0047] The compressive strength test is used to measure the influence of admixture factors on the solidification effect of waste residue. The commonly used method for determining compressive strength is generally based on the compressive strength of cement mortar, according to the "Specification for Cement-Soil Mix Design" (JGJ / T 233-2011). This involves using a 70.7mm × 70.7mm × 70.7mm cube specimen, placing it under a compression testing machine until failure, recording the load at failure, and obtaining the compressive strength value of the specimen. This test uses a TYE-600E universal compression testing machine. The steps for determining the compressive strength of the specimen are as follows:

[0048] (1) Determine the base area A of the cubic specimen. Set the parameters such as the age of the pressure testing machine, specimen size, bearing area, maximum load and loading rate, and conduct tests at ages of 14d, 28d and 56d respectively;

[0049] (2) Place the sample in the designated position and press the pressure testing machine at 1.5 kN·s. -1 The load was continuously and uniformly applied at a rate until the specimen failed, and the load P at the failure point was recorded.

[0050] The compressive strength of the specimen is calculated according to Formula 1. The average of the three values ​​is taken as the final compressive strength. If the measured value of a single specimen exceeds or falls below 15% of the average value, the value must be discarded. The average value of the measured values ​​of the specimens is the compressive strength.

[0051] fu = P / A (Formula 1);

[0052] Where: fu is the compressive strength, in MPa;

[0053] P is the destructive load, in units of MN;

[0054] A is the base area of ​​the cubic specimen, in m². 2 .

[0055] The test results are shown in Table 2:

[0056] Table 2 shows the compressive strength (in MPa) of the modified concrete obtained in Examples 1-9.

[0057] Example 1 0.11 0.14 0.1 0.12 Example 2 0.11 0.08 0.11 0.10 Example 3 0.1 0.16 0.21 0.16 Example 4 0.14 0.33 0.11 0.19 Example 5 0.29 0.09 0.26 0.21 Example 6 0.25 0.19 0.2 0.21 Example 7 0.14 0.13 0.1 0.13 Example 8 0.13 0.12 0.16 0.14 Example 9 0.21 0.08 0.2 0.16

[0058] Table 2 shows that the curing effect is better when the reinforcing agent is blast furnace slag than the other two materials. The curing effect of pure cement and fly ash is comparable, and the compressive strength of fly ash is slightly higher than that of pure cement. The compressive strength of the specimens generally increases with the increase of the proportion of curing material.

[0059] II. Shear Strength Test

[0060] This experiment was conducted using a multifunctional concrete / rock shear apparatus. The steps for determining the shear strength of the specimens were as follows:

[0061] (1) Prepare and cure the test specimens according to regulations, and cure them to the required age for testing;

[0062] (2) Place the cured specimen in the shear box, and then place the load transfer plate and roller array on top. When installing the normal and shear loading systems, ensure that the resultant force of the normal force and the shear force passes through the midpoint of the shear plane;

[0063] (3) Install instruments to measure normal and shear displacement. The support point of the measuring rod should be set outside the range of influence of shear deformation. The measuring rod and the instrument frame should have sufficient rigidity.

[0064] (4) The normal load is applied in 5 equal levels according to the design maximum normal load, and 3 specimens are tested for each level of load.

[0065] (5) Apply the test normal load and measure the normal displacement. When the difference between two consecutive normal displacement readings does not exceed 1%, start applying the shear load. During the shearing process of the specimen, the normal stress should be kept constant. The initial rate of applying the shear load is 0.4 MPa / min. Select an appropriate load interval to measure and record the shear strain value. When the horizontal deformation caused by the applied shear load is more than about 1.5 times that of the previous load deformation, halve the load application rate and reduce the measurement interval until shearing occurs. Record the shear failure load.

[0066] (6) After the specimen is sheared, a shear load is applied again under the same normal stress. The residual shear load that continuously undergoes large displacements under approximately equal shear stress is measured;

[0067] (7) Remove the normal stress, describe the shear surface, record the shear surface undulation difference, aggregate and interface damage, draw the cross-sectional height change curve in the shear direction, and measure the shear area.

[0068] Calculate the normal stress and shear stress under each level of normal load using formulas 2 and 3, and retain the results to the nearest 0.01 MPa.

[0069]

[0070]

[0071] In the formula: σ i —Normal stress, in MPa;

[0072] τ i —Shear stress, in MPa;

[0073] F σ —Total normal load, in N;

[0074] F τ —Shear load should deduct the frictional resistance of the roller bearing, in N;

[0075] A – Effective shear area of ​​the shear plane, in mm. 2 .

[0076] The average value of the measurements from multiple specimens is taken as the shear stress under the normal load of this level.

[0077] Based on the normal stress and shear stress under each level of normal load, plot the σ-τ line on the coordinate graph, and obtain f′ and c′ in Formula 4 using the least squares method or graphical method:

[0078] τ=σf′+c′ (Formula 4)

[0079] In the formula: τ—ultimate shear strength, in MPa;

[0080] σ — Normal stress, in MPa;

[0081] f′——Friction coefficient;

[0082] c′——cohesion, in MPa.

[0083] The test results are shown in Figure 3.

[0084] Table 3 Shear strength of the cured materials obtained in Examples 1-9

[0085]

[0086]

[0087]

[0088] As can be seen from the table above, in terms of shear strength, the curing effect of adding blast furnace slag and fly ash is better than that of simply adding cement. The shear strength of the specimens with blast furnace slag generally increases with the increase of the curing material content, while the shear strength of the specimens with fly ash and those with cement is less affected by the amount of curing material.

[0089] III. Water Stability

[0090] The water stability of monazite waste solidification is primarily assessed after the solidified monazite waste has been saturated with water. The changes in the mechanical properties of the modified waste after water saturation are further examined by testing the strength (compressive strength and shear strength) of the samples after immersion in water. The experiment will use a vacuum saturation method to saturate the prepared samples (70.7×70.7×70.7mm cubes and cylinders with a diameter of 50mm and a height of 50mm), and then conduct strength tests on the samples in the saturated state to analyze the water stability of the monazite waste solidification.

[0091] The strength loss rate is used to quantitatively represent the strength loss of the solidified monazite waste residue after immersion in water for 1 day. The formula for calculating the strength loss rate is as follows:

[0092] Wf=(F1-F2) / F1 (Formula 5)

[0093] Where: F1—compressive strength / shear strength at the standard curing age, MPa;

[0094] F2—Compressive strength / shear strength (MPa) after standard curing and saturation with water in a vacuum water-retaining machine upon reaching the specified age.

[0095] The test results are shown in Table 4.

[0096] Table 4 Statistical results of shear tests on water-stabilized test blocks

[0097]

[0098]

[0099]

[0100] As shown in the table, the shear strength of the specimens decreased to varying degrees after soaking in water. The specimens incorporating blast furnace slag experienced the greatest strength loss, reaching 45.5%, and this loss decreased with increasing incorporation ratio. The specimens incorporating pure cement showed the second-highest strength loss, while those incorporating fly ash showed the least. Among the water-stabilized specimens, fly ash exhibited the best solidification effect, followed by blast furnace slag, with pure cement showing the worst effect. The shear strength increased with increasing solidification material incorporation ratio.

[0101] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative intent, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for solidifying monazite waste, characterized in that, The steps are as follows: Cement, monazite waste, admixtures, reinforcing agents, and water are mixed to obtain mortar; the mass ratio of cement, monazite waste, admixtures, and water is 1:5-8:0.015:0.45-2.

0. The mortar is solidified to obtain solidified monazite waste residue; The additive is a naphthalene-based water-reducing agent; The reinforcing agent is fly ash.

2. The curing method according to claim 1, characterized in that, The cement includes ordinary Portland cement.

3. The curing method according to claim 1, characterized in that, The mass ratio of cement to reinforcing agent is 1:

1.

4. The curing method according to claim 1, characterized in that, The water-cement ratio of the mortar is 0.45 to 2.

0.

5. The curing method according to claim 1, characterized in that, The mixing process includes: first mixing the cement, monazite waste, admixtures, and reinforcing agents to obtain a first mixture; and second mixing the first mixture with water.

6. The curing method according to claim 5, characterized in that, Both the first and second mixing were carried out under stirring conditions; the first mixing time was 5 minutes; and the second mixing time was 15 minutes.

7. The curing method according to claim 1, characterized in that, After curing, the process further includes curing the obtained solid material; the curing temperature is 18-22°C, the curing time is 14-56 days, and the relative humidity during curing is ≥95%.

Citation Information

Patent Citations

  • A method for curing radioactive waste resin with cement using naphthalene-based water-reducing agents

    CN102262911A